KEBIJAKAN AKSES PENDIDIKAN MELALUI SISTEM PENERIMAAN MURID BARU (SPMB) KABUPATEN WONOGIRI 2025 - Rusmini, Rusmini; Iwan Ristanto (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2025)
In an effort to achieve equitable access to education, the government has established the New Student Admission System (SPMB) policy. However, the policy still faces a number of challenges, such as manipulation of domicile data to bypass the zoning system, disparities in the number and quality of learning groups, inequalities in school quality, and the public’s limited understanding of the available admission pathways. This paper aims to contribute to the improvement of the SPMB system for the 2025/2026 academic year, with a particular focus on its implementation in Wonogiri Regency. The method employed is a descriptive policy analysis using a qualitative approach, supported by data triangulation and stakeholder participation.Findings from previous SPMB implementation in Wonogiri indicate that high-performing schools tend to be oversubscribed, while schools in peripheral areas suffer from low enrollment. This condition highlights the need for adjustments to the zoning system that go beyond geographic distance to include factors such as school capacity, facilities, and the socio-economic context of the community. This article presents a critical review of the 2025 SPMB implementation, focusing on: 1) zoning adjustments based on population distribution maps and school capacity; 2) the use of a digital system with geo-tagging for domicile data verification; and 3) strengthening affirmative action and scholarships for students from underprivileged families.